The Creative Imagination In the structure of Designed work: أيمان طه ياسين (Al-Academy, 2016)
In the marsh of the vast technical development and its reflections on the public life in all of its forms man lives in the shade of this and that and he is in a disprate need to took attentively at his reality through a new artistic vision which the imagination gives it , its value, from this point we find the designers pay great efforts in creating advertising designs that creation and fertile imagination are consisting one unit, and through her flying study on the reality of employing the creative imagination in the designing of printed advertisements, the researcher submitted her questions where some of which are: -What are the requirements of employing the creative imagination in the designing process? And -What are the machineries of the creative performance in the reality of these designing? Chapter one tackled the research problem, its importance, its goals, and its limits. While chapter two tackled the "theoretical frame" into two inquiries about "imagination and memory, the concept of creativeness, creative imagination" as for the second inquiry, it tackled the subject of "the adaptation of imagination in the structure of creative artistic work". Then she illustrates the most important outcomes of the theoretical frame. Then the researcher demonstrates the research procedures in chapter three. She analyzed the samples in chapter four and she got out the research results which some of which were: 1-The simplicity and reference condensing are the prevailed in the designing of the advertisements and they respond to the requirements of the designing function in the speed of affecting and effecting. And the treatment style reflect the mental and artistic ability of the designer. As in samples (3, 4, 5).2-The specialized experience has great role in finding the balances which found the creation action in the set up of the image structure of the imaginative root. 3-Of the treatments that the designer can use as machineries for creative acting in the reality of the designing work. The form metaphor / form reducing and condensing, form exaggerating /reducing and condensing /form exaggerating / activating the trend in away evoke the questions and the meditations in the receiver / colours treatment / the varying in volumes and areas